Social influence in family life: ethnic group and intercultural relations - Souza Filho, Edson Alves de; Beldarrain-Durandegui, Angel (Paidéia (Ribeirão Preto), 2010)
Remembrances of young Jews and non-Jews were analyzed to infer patterns of social influence adopted by their parents and ancestors. We suppose that the ways of influencing among Jews is related to a search of autonomy, differentiation and demarcation of interindividual/intergroup boundaries, which is the opposite among non-Jews. The participants were students from two private high schools. Subgroups were formed according to surnames: Ashkenazim (German Jews), Ashkenazim/Sephardim (Iberian Jews), Jews/Non-Jews and Non-Jews. They reported remembrances of parents and ancestors, going back until the 5th generation; simulated a self-introduction to a person with a different religious background; indicated places abroad where they would live; and mentioned ten surnames other than their families'. Influence models of Jewish students emphasized individual and group aspects of family life, while non-Jews emphasized inter-individual relationships. The Jews' self-introduction to others revealed emphasis on their own and others' group aspects, while non-Jews emphasized courtesy/politeness.